Stroke Pattern In Diabetic Vs Non-Diabetic Patients - Habib, Muhammad Kashif; Hussain, Muhammad Waseem; Rukhsar, Gul; Ahmad, Waleed; Din, Zia Ud; Hidayat, Saba (Biological and Clinical Sciences Research Journal, 2025)
Stroke is a leading cause of morbidity and mortality worldwide, with diabetes mellitus being a major risk factor influencing stroke patterns. Understanding the differences in stroke types and associated risk factors in diabetic and non-diabetic patients can help optimize prevention and management strategies. Objective: This study aimed to compare stroke patterns in diabetic and non-diabetic patients, focusing on the prevalence of ischemic and hemorrhagic strokes and associated vascular risk factors. Methodology: A comparative cross-sectional study was conducted on 60 patients aged 25 years and above who were equally divided into diabetic and non-diabetic groups based on documented medical history and standard diagnostic criteria. Stroke diagnosis was confirmed via neuroimaging with classification into ischemic or hemorrhagic subtypes. Results: The diabetic group had a mean age 55.03±10.09 years while non-diabetics averaged 56.77±11.02 years. BMI was notably higher in diabetics 29.43±2.35 kg/m² vs. 25.82±2.13 kg/m². Hypertension and dyslipidemia were more frequent in diabetics at 46.7% and 36.7% respectively compared to 20.0% and 13.3% in non-diabetics. A history of cardiovascular disease was significantly higher in diabetics, 26.7% vs. 6.7%. Ischemic strokes were more frequent among diabetics, 83.3%, compared to non-diabetics, 56.7%. Conclusion: Diabetes considerably influences stroke patterns with a higher prevalence of ischemic strokes and associated vascular risk factors.